2019
DOI: 10.1002/lt.25675
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Outcome of Acute‐on‐Chronic Liver Failure After Surgical Interventions

Abstract: Acute-on-chronic liver failure (ACLF) is a syndrome with high short-term mortality. Precipitating events, including hemorrhage and infections, contribute to ACLF development, but the role of surgery remains unknown. We investigated the development of ACLF in patients with cirrhosis undergoing surgery. In total, 369 patients with cirrhosis were included in the study. The clinical and laboratory data were collected prior to and on days 1-2, 3-8, and 9-28, and at 3 and 12 months after surgery. Surgery type was cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
35
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 12 publications
1
35
0
5
Order By: Relevance
“…Complications of liver cirrhosis such as portal hypertension, ascites, malnutrition, renal dysfunction, or coagulopathy in addition to operative trauma and general anesthesia provoke various complications, resulting in a prolonged hospital stay and higher costs. The increased risk of mortality in patients with LC is the consequence of elevated bacterial infection rates, higher bleeding complications, and postoperative development of acute-on-chronic liver failure (ACLF) [ 7 ]. The surgical outcome depends on the severity of the underlying LC and the operative procedure [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Complications of liver cirrhosis such as portal hypertension, ascites, malnutrition, renal dysfunction, or coagulopathy in addition to operative trauma and general anesthesia provoke various complications, resulting in a prolonged hospital stay and higher costs. The increased risk of mortality in patients with LC is the consequence of elevated bacterial infection rates, higher bleeding complications, and postoperative development of acute-on-chronic liver failure (ACLF) [ 7 ]. The surgical outcome depends on the severity of the underlying LC and the operative procedure [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we showed that the outcome in patients with cirrhosis undergoing either surgery or TIPS is mainly determined by ACLF itself. ( 9 , 10 ) In the case of gastrointestinal bleeding, we demonstrated that TIPS improves survival and the rebleeding rate in patients with ACLF. ( 10 ) Currently, the Child‐Turcotte‐Pugh (CTP) score and Model for End‐stage Liver Disease (MELD), among others, ( 11 , 12 ) are the most commonly applied prognostic models to stratify patient outcome after surgery or TIPS.…”
mentioning
confidence: 91%
“…Even though there has been substantial progress in the fields of hepatology and surgery in managing patients with cirrhosis, surgery-associated AD and mortality remains high and correlates with severity of liver disease (Friedman, 2010 ; de Goede et al, 2012 ). Recently, the role of surgery as a precipitating event for ACLF development has been characterized, resulting in high rates of ACLF development even after electively performed surgical procedures (Klein et al, 2020 ; Chang et al, 2021 ). Therefore, in many hospitals, with the presence of cirrhosis especially in advanced stages is considered a contraindication for all kinds of surgery.…”
Section: Introductionmentioning
confidence: 99%